Humoral response of chicken infected with the microsporidium Encephalitozoon hellem - Saková, K; Sak, B; Ditrich, O; Kvác, M (Parasitology research, 2006)
Chicken (Gallus gallus) were used as the experimental model for study of immune response against the microsporidium Encephalitozoon hellem (Didier et al., J Inf Dis 163:617-621, 1991) infection in birds. Two-day-old chicken were infected perorally or intraperitoneally with a dose of 10(7) spores of E. hellem. The anti-E. hellem immunoglobulin (Ig)A, IgY, and IgM antibody responses in sera and dropping sample extracts were determined by enzyme-linked immunosorbent assay. Results have shown specific antibody production in sera and intestinal secretions of infected birds. Chicken inoculated perorally developed the lowest antibody response. Microsporidian spores were not identified in the smears from cloacal swab samples of individual chicken. Intestinal segment cultures of perorally infected chicken cultivated in vitro showed the highest production of specific IgY and IgA antibodies in jejunum segments. In the further course of infection, the colon produced the highest amount of IgA, and the ileum and colon produced the highest amount of IgY.
Keywords: kur domácí; encephalitozoonóza; Feces; modely nemocí na zvířatech; Immunoglobulin M; Cloaca; Chickens; imunoglobulin M; kloaka; Gastrointestinal Tract; Antibodies, Fungal; Spores, Fungal; imunoglobuliny; protilátky fungální; ELISA; Encephalitozoon; Time Factors; spory hub; Enzyme-Linked Immunosorbent Assay; Animals; zvířata; časové faktory; Disease Models, Animal; gastrointestinální trakt; imunoglobulin A; Encephalitozoonosis; Immunoglobulin A; Immunoglobulins; feces